AmBisome Induced Avascular Necrosis of the Alae of the Nose of a very young girl suffering from Kala‐azar – a Case Report. Issue 6 (21st October 2016) - Maruf, Shomik; Nath, Proggananda; Aktar, Fatima; Basher, Ariful
Abstract: Although liposomal amphotericin B (AmBisome) is considered as the first‐line treatment for New Kala‐azar, there is not enough evidence on the dosage formulation in children and its effect on them. Being considered as the safest drug for treatment of Kala‐azar, this case of AmBisome‐induced avascular necrosis now gives rise to the question; whether it is actually safe enough and if a dosage modification is needed in case of children. This so far, to the best of our knowledge, is the first instance of such severe adverse event due to AmBisome administration.